A One-Pot Synthesis of Sulfonyl Amidinesvia Three-Component Reaction Under Mild and Solvent-Free Conditions - Chiaa Adiche; Douniazad El Abed (Journal of Current Scientific Research, 2021)
A convenient one-pot synthetic protocol for the preparation of sulfonyl amidines has been developed. The procedure combines three-component reaction of sulfonyl azide, methyl propiolate and secondary cyclic amine coupling in one sequence without any solvent or catalyst and at room temperature. The reaction proceeds smoothly and a variety of desired sulfonyl amidines were obtained in moderate to good yields. This protocol has synthetic advantages in terms of low environmental impact and very short reaction time.
Keywords: Multicomponent reactions